Prvine zakonodajne sledi v funkciji transparentnosti zakonodaje - Igličar, Albin (Pravni letopis, 2015)
A legislative footprint in Europen Union is a comprehensive public record of lobbyists' influence on a piece of legislation. Lobbying needs to become more transparent and open to public scrutiny. A special aspect of the principle of public procedure spreads already to the so-called pre-legislative procedure, going on in ministries, before the bill is sent to the parliament. After submitting a draft statute we can distinguish three basic phases in it: the first, the second and the third reading of the draft statute with the final vote on the statute. In the article the elements of public and of legislative footprint are presented on example of Real Property Tax Act.
Keywords: lobiranje; odločanje; Slovenia; Slovenija; zakonodajni postopek